Leveduras isoladas de ninhos de Acromyrmex Balzani (Hymenoptera: Formicidade) de áreas de cerrado do Estado do Tocantins - Melo, Weilan Gomes da Paixão [UNESP] (2014)
Leafcutter ants of the genera Atta and Acromyrmex maintain a mutualism with basidiomycetous fungus Leucoagaricus gongylophorus cultivated for food, which is responsible for the production of extracellular enzymes that degrade plant material transported into the nests. Besides the mutualistic fungus, a diverse microbiota comprising filamentous fungi, yeasts and bacteria is present in the nest and also contribute to the degradation of plant tissues. The yeast community of the fungus garden and waste material from nests of the leaf-cutting ant Acromyrmex balzani in preserved and disturbed areas of cerrado in Palmas, Tocantins was characterized and the ability of these strains to produce extracellular enzymes was investigated. Twenty-four nests (14 in preserved environment and 10 in disturbed environment) were sampled, and a total of 720 yeast isolates was obtained, comprising 52 species belonging to 20 genera. The richness and diversity of species in preserved environment were higher compared to the disturbed environment, as well as diversity in waste material was higher compared to the fungus garden. The most prevalent species was Cryptococcus laurentii, with 132 isolates, followed by Trichosporon mycotoxinivorans, with 61 isolates. The basidiomycetous yeasts were prevalent in the nests of A. balzani, both in fungus gardens as with the discarded material. Prevalent ascomycetous were Aureobasidium and Meyerozyma. Based on sequence analysis of the D1/D2 region of LSU rRNA putative new species were found of the genera Starmerella and Bullera. Seven hundred and eleven strains of the 720 recovered ones were tested for their ability to produce amylase, cellulase, ligninases, lipase, xylanase, pectate lyase and polygalacturonase. Physiological tests for their ability to assimilate glucose, cellobiose, galacturonic acid, maltose and xylose through isolated strains of these environments were also conducted. About 95% of the strains tested showed...